The opportunity index : a solution-based framework to dismantle the racial wealth gap - Lewis, Gavin (Ascent Audio, 2023)
In The Opportunity Index, BlackRock managing director and cofounder of the #Talkaboutblack movement, Gavin Lewis, skillfully plots the origins of the racial wealth gap and its impact on the inequalities faced by the Black community today. Weaving a personal and at times moving narrative through some of the most disruptive events of our time, he offers a blueprint for businesses and individuals to understand the risks and opportunities presented by inequality and issues an urgent call to action. The Opportunity Index also presents: a root cause-oriented and solutions-focused exploration of the racial wealth gap and its role in social, health, and opportunity inequality; a perspective that moves beyond the typical workplace discussion to explore the deeper truths about society and the role of capitalism; and the lessons learned from the #BlackLivesMatter, #MeToo, and climate change movements and how these provide case studies for real and lasting change. An eye-opening and insightful treatment of what equity and access mean in the context of international finance, The Opportunity Index will earn a place in the libraries of finance professionals, business leaders, teachers, academics, community leaders, diversity, equity, and inclusion experts, and anyone else with an interest in racial, social, and economic fairness around the world.